SOCIO-CULTURAL DETERMINANTS OF ADOLESCENTS SEXUALAND REPRODUCTIVE BEHAVIOUR IN KEFFI LOCAL GOVERNMENT AREA, NASARAWA STATE-NIGERIA - Deborah Gwom Dung; Mamman Matthew Samuel; Umar Haruna Yashim (International Studies Journal)
Sexual and reproductive behaviour has become a major issue of concern in recent times. This is because the incidence of sexual intercourse has become prevalent among adolescents. Adolescents engage in several risky sexual and reproductive behaviour like the early sexual debut, having multiple sexual partners, unwanted pregnancy and unsafe abortion. This is although society frowns at this incidence as adolescents are expected to abstain from sex. Thus, the objective of this paper is to x[1]ray the factors that influence the sexual and reproductive behaviour among adolescents in Keffi A descriptive research design was adopted. Primary data were obtained using both quantitative and qualitative methods. In the survey, 344 questionnaires were distributed among the sample size using multi-stage sampling techniques of Wards, settlements, households and individualsand six focus group discussions were also conducted. Also, qualitative data was collected using Focus group discussion among adolescents. Descriptive and inferential statistics of the data were carried out using a statistical package for social sciences (SPSS) Windows version 25.0. Findings reveal that the factors that determine the sexual and reproductive behaviour of adolescents are largely curiosity, peer pressure and poverty.Thus, the study recommend that parents and guidance provide counseling to their children and wards about sex so they don't have to give in to peer pressure or become curious about sexual intercourse.